2013
DOI: 10.1155/2013/630683
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Papillomavirus Clastogenic Effect Analyzed in Comet Assay

Abstract: Bovine papillomavirus (BPV) is an oncogenic virus related to serious livestock diseases. Oncoproteins encoded by BPV are involved in several steps of cellular transformation and have been reported as presenting clastogenic effects in peripheral lymphocytes and primary culture cells. The aim of this study was to evaluate the clastogenic potential of BPV types 1, 2, and 4 by comet assay. Peripheral blood was collected from 37 bovines, 32 infected with different levels of papillomatosis (12 animals have no affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
0
20

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(89 citation statements)
references
References 28 publications
8
61
0
20
Order By: Relevance
“…Although current studies have shown the expression of E5 and L1 of BPV-1 and -2 in CD4+ and CD8+ cells (Roperto et al 2008(Roperto et al , 2011, as well as BPV activity in PBMCs by comet assay in both symptomatic and asymptomatic cattle (Araldi et al, 2013a), the presence of BPV virions in PBMCs have not been identified. In this study, PCR results showed the co-infection of BPV-1, -2 and -4 in PBMCs, which has already been described in peripheral blood (Carvalho et al, 2013;Araldi et al, 2014a).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Although current studies have shown the expression of E5 and L1 of BPV-1 and -2 in CD4+ and CD8+ cells (Roperto et al 2008(Roperto et al , 2011, as well as BPV activity in PBMCs by comet assay in both symptomatic and asymptomatic cattle (Araldi et al, 2013a), the presence of BPV virions in PBMCs have not been identified. In this study, PCR results showed the co-infection of BPV-1, -2 and -4 in PBMCs, which has already been described in peripheral blood (Carvalho et al, 2013;Araldi et al, 2014a).…”
Section: Discussionmentioning
confidence: 71%
“…The same authors also suggest that the peripheral blood could act as a viral disseminator (Král et al, 2015). Recent studies have reinforced the role of peripheral blood mononuclear cells (PBMCs) as virus carriers, showing that BPV is present in CD4+ and CD8+ lymphocytes (Roperto et al, 2008;Araldi et al, 2014a) and the detection of BPV activity in PBMCs by the comet assay (Araldi et al, 2013a) and flow cytometry (Roperto et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to Ribeiro et al (2003) and Frieauff et al (2013), for the MNT in polychromatic erythrocytes, analysis of 2000 cells is recommended, whereas for the MNT in binucleated lymphocytes, 1000 cells are recommended for analysis. In the comet assay, only 100 cells need to be analyzed because of the high sensitivity of this assay in detecting free DNA fragments (Araldi et al, 2013). These values for cells analyzed are based on statistical considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Micronuclei are chromosomal fragments or whole chromosomes that are lost during cell division, which can be detected as extra-chromosomal particles (Frieauff et al, 2013), indicating chromosome breakage (clastogenicity), which can lead to genomic instability, an indicator of oncogenic processes (Fenech, 2000;Araldi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%